The Case for Improved Interprofessional Care: Fatal Analgesic Overdose Secondary to Acute Dental Pain during Pregnancy - Sarah K. Y. Lee; Rocio B. Quinonez; Alice Chuang; Stephanie M. Munz; Darya Dabiri (Case Reports in Dentistry)
Prenatal oral health extends beyond the oral cavity, impacting the general well-being of the pregnant patient and her fetus. This case report follows a 19-year-old pregnant female presenting with acute liver failure secondary to acetaminophen overdose for management of dental pain following extensive dental procedures. Through the course of her illness, the patient suffered adverse outcomes including fetal demise, acute kidney injury, spontaneous bacterial peritonitis, and septic shock before eventual death from multiple organ failure. In managing the pregnant patient, healthcare providers, including physicians and dentists, must recognize and optimize the interconnected relationships shared by the health disciplines. An interdisciplinary approach of collaborative and coordinated care, the timing, sequence, and treatment for the pregnant patient can be improved and thereby maximize overall quality of health. Continued efforts toward integrating oral health into general healthcare education through interprofessional education and practice are necessary to enhance the quality of care that will benefit all patients.